(untitled) (Journal of the College of Basic Education, 2025)
Students’ attitudes toward learning the English language can vary widely based on several factors such as Personal Factors, Pedagogical Factors, and Environment Factors. Therefore, there is a need to understand these factors in order to help educators to create more effective English language learning environment that improve students’ their attitudes toward the language. Thus, the present study aims to investigate the main factors that can affect Iraqi student’s attitude toward learning English as a foreign language. The study conclude that while students are generally positive toward learning English, targeted improvements in pronunciation support and learning environment could enhance their experience further The study adopted a questionnaire which contains three parts each part describes different data which related to the topic. The data of the study was selected randomly from the population at the Department of Philosophy/ College of Arts, Mustansiriyah University for all stages. The results are analyzed through descriptive statistics of the data through SPSS 26 software program.